(untitled) (International Bulletin of Applied Science and Technology, 2025)
The article examines the key tasks and functions of investigative units in the process of solving crimes amid the modernization of criminal procedure legislation in the Republic of Uzbekistan. The author emphasizes the role of investigative-operational groups as an effective organizational mechanism that ensures a prompt response to reports of crimes. The paper analyzes legal gaps in the current legislation regarding the regulation of such groups’ activities and offers recommendations for improving coordination between investigators and operational officers. Special attention is given to the role of the investigator as a coordinator responsible for the completeness and objectivity of the preliminary investigation, as well as to the issues of procedural independence and coherence in the actions of investigative-operational group members. The study draws on opinions from Uzbek and international legal scholars, along with references to the Criminal Procedure Codes of Uzbekistan and Russia.